IBU HAMIL DAN BALITA PELAYANAN KESEHATAN PADA IBU HAMIL DAN BALITA DI PUSKESMAS KEBOMAS KABUPATEN GRESIK - Shinta Puspitasari Alif (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2022)
The paradigm of population problem management and development oriented to population control and decreased fertility, then turned into a broader approach, namely focusing on reproductive health and efforts to fulfill reproductive rights. Thus the treatment of maternal and child health, family planning (KB), adolescent reproductive health, prevention and control of sexually transmitted infections (IMS) including HIV/ AIDS and elderly reproductive health (elderly) undergo changes. This community service activity begins with sharing a leaflet and video education about the health of pregnant women and toddlers by conducting health education about the benefits of conducting an integrated ANC and also how to do an integrated ANC in pregnant women in the working area of ​​the Kebomas Puskesmas Gresik Regency. Conduct health education about the prevention of hypertension in pregnant women, the causes of hyperemesis gravidarum, stunting prevention methods in toddlers, as well as health care in toddlers to avoid diseases such as fever, flu and diseases that interfere with the growth of toddlers in the work area of ​​Kebomas Puskesmas Gresik Regency. It is expected that health workers are routinely both month or every week to conduct an evaluation of health services for pregnant women and toddlers at the Kebomas Puskesmas Gresik Regency in order to be sustainable and improve the quality of public health in the working area of ​​the Kebomas Puskesmas Gresik Regency